Respuesta :
Answer:
subtract -3
Step-by-step explanation:
–3 + 4x = 9
Add 3 to each side
This is the same as subtracting -3
-3 + 4x - (-3) = 9 - (-3)
4x = 9 +3
4x = 12
Answer:
She should subtract -3 from both sides
Explanation:
To solve this problem you need to isolate the variable. To do that, you would first subtract both sides by negative three and then divide both sides by 4.
Here is what that would look like:
-3 + 4x = 9
-3 - (-3) + 4x = 9 - (-3)
4x = 12
4x / 4 = 12 / 4
x = 3
She should subtract -3 from both sides
Explanation:
To solve this problem you need to isolate the variable. To do that, you would first subtract both sides by negative three and then divide both sides by 4.
Here is what that would look like:
-3 + 4x = 9
-3 - (-3) + 4x = 9 - (-3)
4x = 12
4x / 4 = 12 / 4
x = 3